MODEL PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DENGAN MENGGUNAKAN MEDIA PERMAIANAN KARUTA DALAM PEMBELAJARAN HURUF HIRAGANA - Swayantika, Nabilla; Dwi Astuti Retno Lestari (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
This study discusses the use of the STAD (Student Teams Achievement Division) learning model using the karuta game media in learning hiragana letters. The use of this model and media includes small groups where learners will work together to match the torifuda cards read by the yomifuda card reader. Reference collection in this research is books, articles, journals and websites. This study aims to determine the steps of using the STAD (Student Teams Achievement Division) learning model using the karuta card media in learning hiragana letters, as well as the advantages and disadvantages of the karuta card media and the STAD learning model in learning hiragana letters using descriptive qualitative research methods the results are obtained on the judgment of the expert (expert judgment). The use of media and learning models aims to be an alternative that can be used during the learning process to make it easier for learners hiragana letters.